Dynamic General Equilibrium Modeling - Heer, Burkhard (Springer, 2017)
Modern business cycle theory and growth theory uses stochastic dynamic general equilibrium models. In order to solve these models, economists need to use many mathematical tools. This book presents various methods in order to compute the dynamics of general equilibrium models. In part I, the representative-agent stochastic growth model is solved with the help of value function iteration, linear and linear quadratic approximation methods, parameterised expectations and projection methods. In order to apply these methods, fundamentals from numerical analysis are reviewed in detail. In part II, the authors discuss methods in order to solve heterogeneous-agent economies. This part of the book also serves as an introduction to the modern theory of distribution economics. Applications include the dynamics of the income distribution over the business cycle or the demographic transition in a large-scale overlapping generations model. In an accompanying home page to this book, computer codes to all applications can be downloaded.